Visual control of locomotion in people with Parkinson's disease - Vitório, Rodrigo [UNESP]; Baptista, André Macari [UNESP] (Springer Nature, 2017)
Vision is intricately linked with action and plays an essential role in guiding safe locomotion in humans. However, vision can influence locomotion of people with Parkinson's disease (PD) in two distinct manners. While visual information such as doorways can trigger freezing episodes during which the patient feels as if the feet are glued to the floor, visual cues (transverse lines placed on the ground) can increase stride length and release freezing episodes. These paradoxical responses to visual information have motivated researchers to investigate the role of vision during locomotion in people with PD. In addition, studying PD as a model, in which the basal ganglia circuits are damaged and walking impairments are evident, may provide insights into the neural control of human locomotion. This book chapter explores how people with PD use visual information while engaged in different real-world walking activities, such as walking on regular pathway and visual cues, avoiding obstacles, and stepping on targets.
Keywords: Basal ganglia; Cues; Eye tracking; Gait; Obstacle; Parkinson's disease; Vision